[substitution method]
9x - 5y =2
3x - 4y =10
Answers
Answered by
0
Answer:
6x - y = -8
Step-by-step explanation:
subtract both the equations.
9x - 5y =2
- 3x - 4y =10
(+) (-)
------------------------------
6x - y = -8
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d00/2b90ef62bc42005b23797cf9ac89ec6d.jpg)
Similar questions
Math,
3 months ago
Science,
3 months ago
Social Sciences,
3 months ago
Math,
7 months ago
Science,
1 year ago
Psychology,
1 year ago